2019
DOI: 10.1136/vetreccr-2019-000828
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spirocercosis in a dog in the UK

Abstract: A 2-year-old female neutered crossbreed dog was presented for evaluation of a 3-day history of haematemesis, melaena and hyporexia. The dog had been imported from a rescue centre in Hungary 4 months prior to presentation. Abdominal CT revealed the presence of a 3 cm×3 cm×4 cm diameter heterogenous intraluminal mass lesion in the gastric cardia, surrounding the ostium of the cardia and continuous with the distal oesophagus. The mass lesion was subsequently surgically resected. Histopathology of the gastric mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Less common conditions associated with CATh include Spirocerca lupi , 17 but to the authors’ knowledge, this has only been identified in the United Kingdom once 18 . However, that case had been imported from Hungary, with infection in mainland Europe considered fairly frequent 19 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Less common conditions associated with CATh include Spirocerca lupi , 17 but to the authors’ knowledge, this has only been identified in the United Kingdom once 18 . However, that case had been imported from Hungary, with infection in mainland Europe considered fairly frequent 19 .…”
Section: Discussionmentioning
confidence: 87%
“…3,4,9,[13][14][15][16] Less common conditions associated with CATh include Spirocerca lupi, 17 but to the authors' knowledge, this has only been identified in the United Kingdom once. 18 However, that case had been imported from Hungary, with infection in mainland Europe considered fairly frequent. 19 Given there is no history of travel abroad in this case, and parasite control has been kept up to date regularly, Spirocercosis or other endoparasite infestation is unlikely.…”
Section: Discussionmentioning
confidence: 97%